A novel variant of NR5A1, p.R350W implicates potential interactions with unknown co-factors or ligands - Gau, Maki; Suga, Ryota; Hijikata, Atsushi; Kashimada, Ayako; Takagi, Masatoshi; Nakagawa, Ryuichi; Takasawa, Kei; Shirai, Tsuyoshi; Kashimada, Kenichi; Morio, Tomohiro (Frontiers in Endocrinology, 2023)
NR5A1 and NR5A2 belong to an orphan nuclear receptor group, and approximately 60% of their amino acid sequences are conserved. Transcriptional regulation of NR5A receptors depends on interactions with co-factors or unidentified ligands. We identified a novel missense variant p.R350W in the ligand-binding domain of NR5A1 in a patient with 46,XY disorder of sex development. In the study, [1] reporter assays demonstrated that R350 is essential for NR5A1; [2] 3D model analysis predicted that R350 interacted with endogenous ligands or unknown co-factors rather than stabilizing the structure; [3] R350 is not conserved in NR5A2 but is specifically required for NR5A1; and [4] none of the 22 known missense variants of the ligand binding domain satisfied all the previous conditions [1][3], suggesting the unique role of R350 in NR5A1. Taken together, NR5A1 would have unidentified endogenous ligands or co-activators that selectively potentiate the transcriptional function of NR5A1 in vivo.